Utilizing blooket the game-based learning platform for introduction to computer security - Bujang Khedif, Lenny Yusrina; Putit, Sulastri; Chachil, Ketty; Bohari, Zubaidah; Abdul Talip, Abdul Hadi (Universiti Teknologi MARA, Kedah, 2023)
Introduction to Computer Security is one of the subjects offered to Diploma in Computer Science students at Universiti Teknologi MARA (UiTM). This subject comprises of 12 topics that cover theoretical principles as well as hands-on lab activities that are often conducted in a physical learning environment. Although we have resumed with physical instruction, online technologies are still being used as a teaching assistance. Various online platforms are employed to attain learning objectives that are convenient for both students and lecturers. Blooket is a game-based learning platform to facilitate educational content distribution, promote interaction between students and lecturers, and provide a variety of learning activities. It allows lecturers to design and customize interactive quizzes, flashcards, and other educational activities for their students. It provides students with a pleasant and engaging way to learn and review various courses in a virtual or blended learning environment. Blooket has been identified and utilized as a teaching aid by lecturers who teach the Introduction to Computer Security course at UiTM Cawangan Sarawak. Therefore, this paper will discourse on the usage of Blooket to assist in teaching and learning.